2017
DOI: 10.1080/00325481.2017.1281084
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of CTPA for the investigation of suspected pulmonary embolism

Abstract: Although CTPA use is increasing, so is the diagnostic yield of PE. In contrast, the rate of incidental PE in those undergoing a CT chest scan for non-PE diagnosis remains relatively low and stable. This suggests that our observed increased use of CTPA is clinically appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
2
16
2
2
Order By: Relevance
“…Current evidence suggests that sensitive D‐dimer testing can be combined with clinical findings and decision rules to exclude PE safely, thus circumventing some avoidable costs and unnecessary imaging . Despite this, there is an increasing use of CTPA in the assessment of patients with cardiorespiratory symptoms . The primary objective of this study was to establish if there was any association between the clinical parameters and biomarkers that influence the decision to order a CTPA and the presence or absence of PE on that test.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that sensitive D‐dimer testing can be combined with clinical findings and decision rules to exclude PE safely, thus circumventing some avoidable costs and unnecessary imaging . Despite this, there is an increasing use of CTPA in the assessment of patients with cardiorespiratory symptoms . The primary objective of this study was to establish if there was any association between the clinical parameters and biomarkers that influence the decision to order a CTPA and the presence or absence of PE on that test.…”
Section: Introductioncontrasting
confidence: 99%
“…14,15 Despite this, there is an increasing use of CTPA in the assessment of patients with cardiorespiratory symptoms. 16 The primary objective of this study was to establish if there was any association between the clinical parameters and biomarkers that influence the decision to order a CTPA and the presence or absence of PE on that test.…”
Section: Introductionmentioning
confidence: 99%
“…Authors found a direct correlation between increased number of CTPA scans and percentage of positive pulmonary embolism (the positive diagnostic yield ranges from 12% to 28.1%), suggesting that the use of CTPA is clinically appropriate. 11 Mountain and colleagues in their multi-center study showed similar findings with association of increasing use of CTPA with increased rates of pulmonary embolism diagnosis. Their study involved 14 clinical sites (15 emergency departments) across Australia and New Zealand consisting of more than 7000 CTPA scans with >94% performed on ≥64-slice CT.…”
supporting
confidence: 59%
“…9 Increased detection of pulmonary embolism seems to be associated with increased use of CTPA, in particular in the emergency department. [11][12][13][14][15][16][17] Although there are no guidelines available about the minimum acceptable yield of CTPA, it is generally agreed that a diagnostic yield of CTPA less than 10% indicates overuse of CTPA as a diagnostic tool. 18,19 Sharma and Lucas recently reported their single center experience of CTPA in the diagnosis of pulmonary embolism over a period of 8 years.…”
mentioning
confidence: 99%
“…Further, no guidelines Research Article Sun, Lei are available about the minimum acceptable diagnostic yield of CTPA, thus leading to overuse of CTPA as a routine diagnostic tool [17,18]. Sharma and Lucas reported the direct correlation between CTPA and positive rates of PE detection with results justifying the increased use of CTPA [19]. However, Mountain et al in their multi-center study showed significant variations in the diagnostic yield of CTPA with some clinical sites producing lower diagnostic yield of less than 15.3% [20].…”
Section: Introductionmentioning
confidence: 99%